Talent transfer: A systematic review - Karlijn van Harten; Kayan Bool; Janiek van Vlijmen; Marije Elferink-Gemser (Bern Open Publishing, 2021)
Background: The effectiveness of traditional talent development (TD) programs can be questioned. Meanwhile, an extra pathway to the top has made its appearance: Talent transfer (TT). The aim of TT is to fast-track talented athletes into the high-performance environment. The first TT initiatives and studies exploring the TT process have been carried out. Objective: This systematic review gives an overview of studies examining TT, by situating TT within the developmental framework, comparing formal and informal TT and investigating the similarities between donor and transfer sports in TT from elite and non-elite level. Methods: A search was conducted on the PubMed and PsychINFO databases. The analysis was done according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta Analyses) statement. Results: After screening on title and abstract and full-text review, five studies remained for inclusion. Although literature is still scarce, results show that TT can serve as an alternative pathway in addition to the traditional TD programs. Literature suggests that similarities between donor and transfer sports are helpful, but this is not a prerequisite for TT. Besides, psychological factors are perceived to play an important role. Results regarding other determining factors of TT are still lacking. Athletes, national governing bodies and TD programs might benefit from this additional pathway, but the effectiveness of formal and informal TT remains unclear. Conclusion: A lot remains unknown about TT, hence future research is needed to increase our understanding of TT and its contribution as an extra pathway to the top.